Parameters influencing the polished stone value (PSV) of road surface aggregates. (15th December 2015) - Descantes, Yannick; Hamard, Erwan
Highlights: We determine the reference value of the new PSV control stone (Herrnholzer granite). We assess polishing machine and specimen preparation biases on PSV test results. We identify flour emery flow rate as a major contributor to polishing machine bias. Road wheel rotation speed is a major scattering source for low PSV aggregates. We make technical recommendations to improve the PSV test method EN 1097-8. Abstract: Results of a European round-robin aiming to identify and quantify scattering sources impacting the polished stone value (PSV) of aggregates, and to assess the reference PSV of Herrnholzer granite, are presented and discussed. This reference value corrected against quartz dolerite control stone is calculated as PSV ref HE = 56.1 ± 0.5. According to variance analysis calculations, PSV scattering sources breakdown into three main components which have been assessed, a random friction tester term and two biases caused by test specimen preparation and polishing machine. Further investigation carried out on machine parameters using principal component analysis (PCA) reveals that narrowing the tolerance on flour emery flow rate should mitigate the machine bias. The results also evidence a higher scattering for low PSV aggregates, and PCA shows that this relates to their higher sensitivity to wheel speed variability not accounted for by the PSV control stone correcting factor. Besides, the results suggest enlarging the validity range of residual friction measured on PSV control stone prescribed by European standard EN 1097-8:2009, and they raise issues relating to test specimen preparation. Eventually, results and suggestions of the present study will be implemented in the ongoing revision of EN 1097-8:2009.